Mitigasi Bencana Untuk Penyandang Disabilitas - Devi, Maria; Sutarto, Sutarto; Ismunandar, Helmi (Medula, 2023)
Indonesia is a country with a high level of vulnerability to natural disasters. Based on data from Indonesia's National Disaster Management Agency (BNPB), it was found that in 2023, 2,669 natural disasters occurred throughout Indonesia. The intensity of the incident with the highest number was forest and land fires 1,624 times. People with disabilities are known to be more vulnerable in emergencies caused by natural disasters. Mitigation, as the first step in dealing with disasters, is the prevention phase followed by the preparedness, emergency response and recovery phases. Measures to reduce potential hazards with an emphasis on Disaster Risk Reduction (DRR) and Disaster Risk Management (DRM) efforts are prioritized. Some inclusive approaches to disaster mitigation for persons with disabilities include planning, preparation, and risk reduction through evacuation training, greater participation of persons with disabilities in disaster coordination and management, and better data management so that integration is not only to fulfill human rights, but through effective programs and policies from pre-disaster, during disaster, and post-disaster stages according to the type and type of disability. The involvement of individuals with disabilities in disaster management systems and processes certainly cannot be achieved without the support and cooperation of all parties, especially the community and government. People with various disabilities from different backgrounds have the opportunity to co-design disaster management and rehabilitation policies, resources or activities. This article will discuss information regarding the preparedness of people with disabilities in the face of disasters.